PERINATAL COMPLICATIONS, ENVIRONMENTAL FACTORS AND AUTISM SPECTRUM DISORDERS - Mandic Maravic, Vanja; Pejovic Milovancevic, Milica; Pekmezovic, Tatjana; Pljesa Ercegovac, Marija; Mitkovic Voncina, Marija; Lecic Tosevski, Dusica (Medicinski podmladak, 2016)
Objectives: Autism spectrum disorders (ASD) are caracterized by qualitative impairment of social interactions, impairment of verbal and nonverbal communication, as well as restricted interests and repetitive behavior. ASD represent a group of complex psychiatric disorders, with both genetic and environmental factors implicated in their etiology. Recent neuroanatomical and epidemiological studies point out to prenatal and early postnatal genesis of ASD. Aim: In this review, we present recent studies that explored the effect of environmental, prenatal and perinatal risk factors on development of ASD. Also, we point out to those factors that have been proven to have the strongest association with ASD, and emphasize a very complex interaction of individual factors that might eventually lead to manifestation of this group of disorders. Conslusion: A precise defining of risk factors might provide more insight not only into etiology of ASD, but also might give us a possibility for early recognition and possible prevention of autism spectrum disorders, especially in susceptible individuals. It is also a first step in defining the basis of the gene-environment interaction mechanism, which might enable the development of an individualised therapeutic approach for this group of disorders. Key words: autism spectrum disorders, autism, risk factor, perinatal complications.